Anion exchange membrane and preparation method thereof
By developing a specific structural polymer that does not contain benzene or carbon bonds, and combined with polyolefin polyitical membrane, it forms a posterior ion exchange membrane with high antioxidant and chemical corrosion capabilities, solving the traditional membrane in the chlorine salt system in the chlorine salt system The problem of corrosion realizes higher stability and service life.
Patent Information
- Application Number
- CN202411432739.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-14
AI Technical Summary
During the process of using an ion exchange membrane to concentrate the chloride salt system, the chloride ions are electrolytically reduced to chlorine, resulting in corrosion of the traditional anion exchange membrane, affecting its stability and service life.
Develop a new anion exchange membrane that includes a polymer with a specific structure that does not contain benzene rings or carbon-carbon double bonds. It stabilizes the free radical reaction of carbon-carbon double bonds through the conjugation effect and improves oxidation resistance. The membrane is composed of a polyolefin porous membrane and a polymer filled in the pores. It forms a three-dimensional network structure through chemical cross-linking to enhance mechanical strength and chemical corrosion resistance.
The pine -ion switching membrane has high ion exchange capacity and low resistance, and has good antioxidant resistance to the electrolytic resolution of the chlorine salt system. It can effectively resist the corrosion of oxidized substances and extend the service life.
Smart Images

Figure CN119327282A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anion exchange membrane, in particular to an anion exchange membrane and a preparation method thereof, belonging to the field of electrochemistry. Background Art
[0002] Over the past 50 years, ion exchange membranes have evolved from laboratory tools to industrial products with significant technological and commercial impact. Today, ion exchange membranes are receiving widespread attention and are successfully used for desalination of seawater and brackish water and treatment of industrial wastewater. They are an effective tool for concentrating or separating foods and pharmaceuticals containing ionic species and for manufacturing basic chemical products. The evolution of ion exchange membranes not only makes the process cleaner and more energy-efficient, but also recycles useful wastewater that is now wasted, thereby making the development of society sustainable.
[0003] However, in the process of using ion exchange membranes to concentrate chloride salt systems, a small amount of chloride ions will be electrolytically reduced to chlorine gas under the action of electric current, which will react with water to form hypochlorous acid anions, which is fatal to traditional anion exchange membranes containing benzene ring structures.
[0004] Therefore, developing an anion exchange membrane that can effectively resist corrosion by oxidizing substances is a huge challenge for the development of ion exchange membranes. Summary of the invention
[0005] The present invention provides an anion exchange membrane with high ion exchange capacity, low resistance and good oxidation resistance to electrodialysis of chloride salt system.
[0006] The present invention also provides a method for preparing an anion exchange membrane. The method is simple to operate and has low cost. The prepared anion exchange membrane can effectively resist corrosion from oxidizing substances.
[0007] In one aspect, the present invention provides an anion exchange membrane comprising a polymer having a structural unit shown in Formula I:
[0008]
[0009] In formula I, A is C, N or O, Cn is a C1-C5 alkylene group, and R1, R2, and R3 are each independently selected from a C1-C6 alkyl group.
[0010] In the anion exchange membrane as described above, the polymer is a cross-linked body comprising the structural unit shown in Formula I.
[0011] The anion exchange membrane as described above comprises a polyolefin porous membrane and the polymer filled in the pores of the polyolefin porous membrane.
[0012] The anion exchange membrane as described above, wherein the thickness of the polyolefin porous membrane is 90 to 120 μm;
[0013] And / or, the pore size of the polyolefin porous membrane is 1 to 1000 nm.
[0014] In another aspect, the present invention provides a method for preparing the anion exchange membrane as described above, comprising the following steps:
[0015] Coating a raw material system including a monomer represented by Formula II on a substrate to initiate a polymerization reaction to obtain the anion exchange membrane;
[0016]
[0017] In the preparation method as described above, the raw material system further comprises a crosslinking agent, an initiator and / or a plasticizer;
[0018] Preferably, the raw material system comprises 70 wt% to 89 wt% of the monomer represented by formula II, 5 wt% to 15 wt% of the crosslinking agent, 5 wt% to 10 wt% of the plasticizer and 1 wt% to 5 wt% of the initiator.
[0019] The preparation method as described above, wherein the cross-linking agent comprises an aliphatic cross-linking agent, preferably ethylene glycol dimethacrylate;
[0020] And / or, the plasticizer includes one or more of phthalates and fatty acid esters;
[0021] And / or, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
[0022] In the preparation method as described above, the polymerization reaction temperature is 80-100° C. and the reaction time is 6-8 hours.
[0023] The preparation method as described above further comprises, after the polymerization reaction is completed, subjecting the polymerization product to a heat swelling treatment in water at 40 to 60°C.
[0024] The preparation method as described above, wherein the substrate is selected from a polyolefin porous membrane;
[0025] Preferably, the thickness of the polyolefin porous membrane is 90-120 μm, and / or the pore size of the polyolefin porous membrane is 1-1000 nm.
[0026] The anion exchange membrane provided by the present invention comprises a polymer with a specific structure, which does not contain a benzene ring or a carbon-carbon double bond, has the characteristics of high hardness and high chemical corrosion resistance, can effectively resist corrosion by oxidizing substances, and effectively solves the problem of the traditional anion exchange membrane's lack of oxidation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a partial diagram of a preparation system according to a specific embodiment of the present invention.
[0028] Description of reference numerals:
[0029] 1-first roller; 2-second roller; 3-third roller; 4-wetting tank; 5-fifth roller; 6-sixth roller; 7-seventh roller; 8-eighth roller. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In one aspect, the present invention provides an anion exchange membrane comprising a polymer having a structural unit shown in Formula I:
[0032]
[0033] In formula I, A is C, N or O, Cn is a C1-C5 alkylene group, and R1, R2, and R3 are each independently selected from a C1-C6 alkyl group.
[0034] The C1-C5 alkylene group may be a C1-C5 straight-chain alkylene group or a C3-C5 cyclic-chain alkylene group. Among them, the present invention prefers C1-C5 straight-chain alkylene groups, which have higher stability than cyclic-chain alkylene groups.
[0035] Considering the flexibility and hydrophilicity of the formed polymer, a C3 alkyl group is preferred; considering the stability and ion exchange capacity of the formed polymer, A=O is preferred.
[0036] R1, R2, and R3 are each independently selected from a C1-C6 alkyl group, and may be a C1-C6 straight-chain alkyl group or a C3-C6 cyclic-chain alkyl group.
[0037] In a specific embodiment, two of R1, R2, and R3 are methyl groups. The inventors have found through experimental research that when two of R1, R2, and R3 are methyl groups, the stability of the anion exchange membrane is better and the ability to resist corrosion by oxidizing substances is stronger. When the carbon chain length of R1, R2, and R3 is longer, Hofmann elimination is more likely to occur, affecting the stability of the anion exchange membrane.
[0038] The anion exchange membrane provided by the present invention includes a polymer having a structural unit as described in Formula I, which can effectively resist corrosion by oxidizing substances and solve the problem of the traditional anion exchange membrane's poor oxidation resistance. The inventor analyzed this and believed that the reason may be that the carbonyl structure in the polymer having the structural unit shown in Formula I can stabilize the free radical reaction of the carbon-carbon double bond through the conjugation effect. In addition, the polymer having the structural unit shown in Formula 1 does not contain a double bond or a benzene ring, which can effectively resist corrosion by oxidizing substances and improve the service life of the formed anion exchange membrane, and the A atom therein can also provide the anion exchange membrane with good ion exchange capacity through the conjugation effect, thereby improving the anion exchange membrane's oxidation resistance under electrodialysis in a chloride salt system.
[0039] Furthermore, in a specific embodiment of the present invention, the polymer is a cross-linked body comprising the structural unit shown in Formula I.
[0040] In detail, the structural units represented by Formula I are chemically cross-linked to form a polymer having a three-dimensional network structure, wherein the structural units represented by Formula I can be interconnected by a cross-linking agent.
[0041] The present invention does not limit the specific type of the cross-linking agent, and a cross-linking agent commonly used in the art, such as an aliphatic cross-linking agent, can be selected.
[0042] When the cross-linked body is included in the anion exchange membrane, the mechanical strength and oxidation resistance of the anion exchange membrane can be further enhanced.
[0043] Furthermore, in a specific embodiment of the present invention, the anion exchange membrane comprises a polyolefin porous membrane and a polymer filled in the pores of the polyolefin porous membrane.
[0044] Among them, the polyolefin porous membrane can provide mechanical support and enhance structural stability, while the polymer can improve oxidation resistance.
[0045] In detail, the present invention does not limit the material of the polyolefin porous membrane, and common materials in the art can be selected, such as PE and PP. Specifically, it can be divided into single-layer PP, single-layer PE, double-layer PP / PE, double-layer PP / PP and three-layer PP / PE / PP, etc., and three-layer PP / PE / PP with high flexibility is preferred.
[0046] The present invention is also not limited to the mass ratio of the polymer to the polyolefin porous membrane. In a specific embodiment, the mass ratio is 1:0.5 to 1:1.5.
[0047] Further, in a specific embodiment of the present invention, the thickness of the polyolefin porous membrane is 90 to 120 μm;
[0048] And / or, the pore diameter of the polyolefin porous membrane is 1 to 1000 nm.
[0049] The thickness of the polyolefin porous membrane in the present invention is the average thickness, and the pore size of the polyolefin porous membrane is the average pore size.
[0050] Specifically, the thickness of the polyolefin porous membrane includes, but is not limited to, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, or a range between any two thereof.
[0051] When the thickness of the polyolefin porous membrane is within the above range, it can avoid the problems of high impedance, increased energy consumption and affected ion transport caused by too high thickness, and low mechanical strength and poor stability caused by too low thickness.
[0052] The pore size of the polyolefin porous membrane includes, but is not limited to, 1 nm, 10 nm, 50 nm, 100 nm, 500 nm, 1000 nm or a range between any two thereof.
[0053] When the pore size of the polyolefin porous membrane is within the above range, it can provide a good supporting structure, improve the mechanical strength of the anion exchange membrane, and at the same time provide an appropriate porosity so that the anion exchange membrane has good ion exchange efficiency.
[0054] In another aspect, the present invention provides a method for preparing the anion exchange membrane as described above, comprising the following steps:
[0055] Applying a raw material system including a monomer represented by Formula II on a substrate to initiate a polymerization reaction to obtain an anion exchange membrane;
[0056]
[0057] In detail, a raw material system including a monomer represented by Formula II is coated on a substrate to initiate a polymerization reaction, and the monomer represented by Formula II is polymerized to obtain a polymer represented by Formula I, thereby forming an anion exchange membrane.
[0058] In one specific embodiment, using Figure 1 Specifically, the production system includes a first roller 1, a second roller 2, a third roller 3, a fifth roller 5, a sixth roller 6, a seventh roller 7, an eighth roller 8, and an impregnation tank 4, wherein the impregnation tank 4 includes a raw material system, the first roller 1, the second roller 2, the third roller 3, and the eighth roller 8 are driven rollers, and the remaining rollers are empty rollers.
[0059] By applying a brake on the second roller 2, the substrate retained on the second roller 2 is tensioned on its length, and then immersed in the raw material system in the impregnation tank 4. The covering material supplied from the first roller 1 is tensioned and expanded in the same way as the substrate. The reinforcing material and the substrate impregnated with the raw material system are double-layered by the sixth roller 6 and directional peeled by the seventh roller 7 and then rolled up on the third roller 3. The other layer of covering material contaminated with part of the raw material system is rolled up and scrapped on the eighth roller 8. The fifth roller 5 plays a role in traction and stretching to prevent the substrate from falling and deforming during the coating process. The content of the raw material system coated on the substrate is adjusted by adjusting the spacing between the two sixth rollers 6.
[0060] It can be understood that after coating, the membrane roll is taken off from the third roller 3 and subjected to polymerization treatment to obtain an anion exchange membrane.
[0061] The covering material mainly acts as a protective layer, and includes but is not limited to polyester film (PET), cellulose film, polyimide film (PI), polyamide film (PA), spandex, and aramid film, preferably PET film, which is low in cost, resistant to high temperatures, and not easily deformed. Before the polymerization reaction, the covering material is peeled off from the substrate of the coating raw material system to avoid the influence of the covering material on the subsequent polymerization reaction.
[0062] In a specific embodiment, the monomer shown in formula II is prepared by a preparation method comprising the following steps: using an alcohol solvent as an ammoniation solvent; using a halogenated alkane R3X (X is a halogen) to ammonize a methacrylic-diamino monomer, wherein the ammoniation reaction parameters are an ammoniation temperature of 40 to 50° C. and an ammoniation time of 6 to 8 hours, to obtain a monomer shown in formula II. The general structural formula of the methacrylic-diamino monomer is as shown in formula III,
[0063]
[0064] The alcohol reagent is one or more of methanol, ethanol, propanol, isopropanol, and butanol, preferably isopropanol with high solubility; the halogenated alkane is one or more of halogenated propane, halogenated butane, halogenated pentane, and halogenated hexane.
[0065] In a specific embodiment, the mass ratio of methacrylic-diamino monomer to alcohol reagent is 1:1-1:3; the molar ratio of methacrylic-diamino monomer to halogenated alkane is 1:1.1-1:1.3.
[0066] Further, in one embodiment of the present invention, the raw material system further includes a crosslinking agent, an initiator and / or a plasticizer;
[0067] Preferably, the raw material system includes 70 wt% to 89 wt% of the monomer represented by formula II, 5 wt% to 15 wt% of the crosslinking agent, 5 wt% to 10 wt% of the plasticizer and 1 wt% to 5 wt% of the initiator.
[0068] When the components are combined within the above mass content range to obtain a raw material system, the synergistic effect of the various components is more conducive to the subsequent polymerization reaction to obtain a polymer as shown in Formula I.
[0069] Further, in one embodiment of the present invention, the crosslinking agent includes an aliphatic crosslinking agent, preferably ethylene glycol dimethacrylate;
[0070] and / or, the plasticizer includes one or more of phthalates and fatty acid esters;
[0071] And / or, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
[0072] The above-mentioned types of cross-linking agents can form chemical bonds between polymer chains, forming a three-dimensional network structure and enhancing the stability of the polymer; the above-mentioned types of plasticizers are mainly used to improve the flexibility and processing performance of the polymer in the polymerization reaction, by inserting into the gaps between polymer chains, lowering the glass transition temperature of the material, improving the processability of the polymer, and making the material easier to shape and process during the processing; the above-mentioned types of initiators can better start the polymerization process and make the polymerization reaction more complete.
[0073] Furthermore, in a specific embodiment of the present invention, the polymerization reaction temperature is 80-100° C., and the time is 6-8 hours.
[0074] In detail, the temperature of the polymerization reaction includes but is not limited to 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C or a range between any two of them, and the time includes but is not limited to 6h, 6.5h, 7h, 7.5h, 8h or a range between any two of them.
[0075] When the polymerization reaction temperature and time are within the above ranges, an anion exchange membrane with more excellent performance can be obtained.
[0076] Furthermore, in a specific embodiment of the present invention, after the polymerization reaction is completed, the polymerization product is subjected to a heat swelling treatment in water at 40 to 60°C.
[0077] The temperature of the heat swelling treatment includes but is not limited to 40° C., 45° C., 50° C., 55° C., 60° C. or a range between any two thereof.
[0078] The thermal swelling treatment can not only wash away the excess plasticizer, but also make the pores left by these non-reactive substances tighter, thereby improving the performance of the anion exchange membrane.
[0079] Further, in one embodiment of the present invention, the substrate is selected from a polyolefin porous membrane;
[0080] Preferably, the thickness of the polyolefin porous membrane is 90 to 120 μm, and / or the pore size of the polyolefin porous membrane is 1 to 1000 nm.
[0081] Specifically, the thickness of the polyolefin porous membrane includes, but is not limited to, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, or a range between any two thereof.
[0082] When the thickness of the polyolefin porous membrane is within the above range, it can avoid the problems of high impedance, increased energy consumption and affected ion transport caused by too high thickness, and low mechanical strength and poor stability caused by too low thickness.
[0083] The pore size of the polyolefin porous membrane includes, but is not limited to, 1 nm, 10 nm, 50 nm, 100 nm, 500 nm, 1000 nm or a range between any two thereof.
[0084] When the pore size of the polyolefin porous membrane is within the above range, it can provide a good supporting structure, improve the mechanical strength of the anion exchange membrane, and at the same time provide appropriate porosity so that the anion exchange membrane has good water permeability and ion exchange efficiency.
[0085] Hereinafter, the anion exchange membrane provided by the present invention is described in detail through specific examples.
[0086] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0087] The sources of raw materials in the embodiments and comparative examples are as follows:
[0088] 3-(Dimethylamino)propyl methacrylate (3-DMAPPMA, Sigma-Aldrich, AR));
[0089] Dimethylaminopropylmethacrylamide (DMAPMA, Macklin's reagent, AR)
[0090] Ethylene glycol dimethacrylate (EGDMA, Anaiji Chemical, AR);
[0091] Unless otherwise specified, other raw materials and reagents are conventional chemical reagents available on the market.
[0092] Example 1
[0093] The anion exchange membrane provided in this embodiment is prepared by a preparation method comprising the following steps:
[0094] 1. 10 kg of 3-(dimethylamino)propyl methacrylate (3-DMAPPMA) was mixed with 20 kg of isopropanol, and 7.9 kg of bromopropane was added. The mixture was reacted at 50° C. for 8 h to obtain a solution including an ammonium monomer.
[0095] 2. Prepare a polymerizable mixed solution based on the mass content of ammonium monomer being 80wt%, the mass content of ethylene glycol dimethacrylate (EGDMA) being 10wt%, the mass content of dioctyl adipate (DOA) being 7wt%, the mass content of azobisisobutyronitrile (AIBN) being 3wt%, and the sum of each component being 100%, and fully dissolve to obtain a raw material system.
[0096] 3. Add the prepared raw material system to the infiltration tank, select three layers of PP / PE / PP (thickness 100μm, width 0.8m, pore size 10nm) as the matrix and PET (100μm) as the covering material, set the coating speed to 0.5m / s, and after coating, obtain the unpolymerized anion exchange membrane roll.
[0097] 4. The anion exchange membrane after coating is rolled off and placed in a vacuum oven for heating and polymerization at 80°C for 8 hours. After the polymerization is completed, the membrane is placed in warm water at 50°C for thermal swelling treatment to obtain an anion exchange membrane.
[0098] Example 2
[0099] The preparation method of the anion exchange membrane provided in this embodiment is basically the same as that in embodiment 1, except that:
[0100] In step 1), 10 kg of dimethylaminoethyl methacrylate (DMAEMA) and 20 kg of isopropanol are mixed, and then 8.6 kg of bromopropane is added, and the mixture is reacted at 50° C. for 8 hours to obtain a solution including ammonium monomers.
[0101] Example 3
[0102] The anion exchange membrane provided in this embodiment is prepared by a preparation method comprising the following steps:
[0103] 1. Mix 10 kg 3-DMAPPMA and 10 kg butanol, add 8.0 kg butyl bromide, and react at 40°C for 8 hours to obtain a solution of ammonium monomer.
[0104] 2. Prepare a polymerizable mixed solution with the mass content of ammonium monomer being 70wt%, the mass content of ethylene glycol dimethacrylate (EGDMA) being 15wt%, the mass content of phthalate being 10wt%, the mass content of azobisisoheptanenitrile being 5wt%, and the sum of all components being 100%, and fully dissolve them to obtain a raw material system.
[0105] 3. Add the prepared raw material system to the infiltration tank, select double-layer PP / PE (thickness 90μm, width 0.8m, pore size 1nm) as the matrix and cellulose membrane (100μm) as the covering material, set the coating speed to 0.5m / s, and after coating, obtain the unpolymerized anion exchange membrane roll.
[0106] 4. The anion exchange membrane after coating is rolled off and placed in a vacuum oven for heating and polymerization at 100°C for 6 hours. After the polymerization is completed, the membrane is placed in warm water at 40°C for thermal swelling treatment to obtain an anion exchange membrane.
[0107] Example 4
[0108] The anion exchange membrane provided in this embodiment is prepared by a preparation method comprising the following steps:
[0109] 1. Mix 10 kg 3-DMAPPMA and 30 kg propanol, add 8.3 kg ethyl bromide, and react at 50° C. for 6 hours to obtain a solution including ammonium monomers.
[0110] 2. Prepare a polymerizable mixed solution according to the mass content of ammonium monomer: 89wt%, mass content of ethylene glycol dimethacrylate (EGDMA): 5wt%, mass content of phthalate: 5wt%, mass content of benzoyl peroxide: 1wt%, and the sum of all components is 100%, and fully dissolve them to obtain a raw material system.
[0111] 3. Add the prepared raw material system to the infiltration tank, select three layers of PP / PE / PP (thickness 120μm, width 0.8m, pore size 1000nm) as the matrix and polyimide membrane (100μm) as the covering material, set the coating speed to 0.5m / s, and after coating, obtain the unpolymerized anion exchange membrane roll.
[0112] 4. The anion exchange membrane after coating is rolled off and placed in a vacuum oven for heating and polymerization at 80°C for 8 hours. After the polymerization is completed, the membrane is placed in warm water at 60°C for thermal swelling treatment to obtain an anion exchange membrane.
[0113] Example 5
[0114] The preparation method of the anion exchange membrane provided in this embodiment is basically the same as that in embodiment 1, except that:
[0115] In step 3), the thickness of the three-layer PP / PE / PP is 85 μm, and the pore size of the three-layer PP / PE / PP is 1200 nm.
[0116] Example 6
[0117] The preparation method of the anion exchange membrane provided in this embodiment is basically the same as that in embodiment 1, except that:
[0118] In step 2), a polymerizable mixed solution is prepared according to the mass content of ammonium monomer being 90wt%, the mass content of ethylene glycol dimethacrylate (EGDMA) being 4wt%, the mass content of dioctyl adipate (DOA) being 4wt%, the mass content of azobisisobutyronitrile (AIBN) being 2wt%, and the sum of each component being 100%, and the raw material system is fully dissolved.
[0119] Example 7
[0120] The preparation method of the anion exchange membrane provided in this embodiment is basically the same as that in embodiment 1, except that:
[0121] In step 4), the polymerization reaction temperature is 75° C. and the time is 9 hours.
[0122] Example 8
[0123] The preparation method of the anion exchange membrane provided in this embodiment is basically the same as that in embodiment 1, except that:
[0124] In step 4), no thermal swelling treatment is performed.
[0125] Comparative Example 1
[0126] The preparation method of the anion exchange membrane provided in this comparative example comprises the following steps:
[0127] 1. 8.9 kg of chloromethylstyrene was mixed with 20 kg of isopropanol, and then 7.9 kg of bromopropane was added. The mixture was reacted at 50° C. for 8 hours to obtain a solution including ammonium monomers.
[0128] 2. Prepare a polymerizable mixed solution with the mass content of ammonium being 80wt%, the mass content of divinylbenzene being 10wt%, the mass content of dioctyl adipate (DOA) being 7wt%, the mass content of azobisisobutyronitrile (AIBN) being 3wt%, and the sum of each component being 100%, and fully dissolve to obtain a raw material system.
[0129] 3. Add the prepared raw material system to the infiltration tank, select three layers of PP / PE / PP (thickness 100μm, width 0.8m, pore size 10nm) as reinforcing material and PET (100μm) as covering material, set the coating speed to 0.5m / s, and after coating, obtain the unpolymerized anion exchange membrane roll.
[0130] 4. The anion exchange membrane roll after the coating is placed in a vacuum oven and heated at 80°C for polymerization for 8 hours. After the polymerization is completed, it is placed in warm water at 50°C for thermal swelling to obtain a formed anion exchange membrane.
[0131] Comparative Example 2
[0132] The preparation method of the anion exchange membrane provided in this comparative example is basically the same as that in Example 2, except that:
[0133] Excluding step 1), the ammonium monomer in step 2 is replaced by chloromethylstyrene, and ethylene glycol dimethacrylate is replaced by divinylbenzene.
[0134] Test Case
[0135] The oxidation resistance of the anion exchange membranes provided in all the embodiments and comparative examples was evaluated mainly by testing the membrane surface resistance and migration number in a sodium hypochlorite solution of a certain concentration at different time periods.
[0136] 1. Soaking in sodium hypochlorite solution
[0137] Small discs with a diameter of 8 cm were cut from the anion exchange membrane prepared continuously industrially. A total of 3 discs were taken and immersed in a 1.0 wt% sodium hypochlorite solution. The membrane surface resistance and migration number were measured at 0, 120 h, 240 h, 480 h, and 720 h, respectively. The test results are shown in Table 1.
[0138] 2. Membrane surface resistance test
[0139] The ion exchange membrane was sandwiched in a double chamber tank equipped with Ag / AgCl electrodes, and both sides of the ion exchange membrane were filled with 0.5mol / L NaCl aqueous solution. The resistance between the electrodes was measured at 25°C using an electrochemical workstation (Ivium-N-Stat). The membrane surface resistance was calculated based on the difference between the resistance between the electrodes and the resistance between the electrodes without the ion exchange membrane. It should be noted that the ion exchange membrane used in the above determination was pre-equilibrated in a 0.5mol / L NaCl aqueous solution, and the test results are shown in Table 1.
[0140] 3. Migration number test
[0141] The ion exchange membrane was clamped in a double-chamber tank equipped with Ag / AgCl electrodes, and 0.1 mol / L NaCl and 0.5 mol / L NaCl were filled on both sides respectively. No current was applied. While stirring the solutions in the two chambers, the potential difference between the two chambers was tested by the Ag / AgCl electrodes to determine the migration number of Cl ions by the anion exchange membrane. The test results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] According to Table 1, the anion exchange membranes provided in Examples 1-8 of the present invention can still maintain a low membrane surface resistance and a high migration number after being soaked in sodium hypochlorite solution for different time periods. Among them, when not treated, the resistance of the anion exchange membranes provided in Examples 1-8 is not higher than 7.21Ω·cm 2 , the migration number is not less than 0.968, and after being treated with 1% sodium hypochlorite solution at room temperature for a certain period of time, the anion exchange membrane provided by Examples 1-8 still maintains relatively excellent performance.
[0146] The resistance of the anion exchange membrane provided in Example 8 increased after 720 h in a 1% sodium hypochlorite solution at room temperature, and was 22.09 Ω·cm 2 , but the migration number is still maintained at 0.701. Therefore, considering comprehensively, the performance of the anion exchange membrane provided by Example 8 is better than that of the anion exchange membranes provided by Comparative Examples 1 and 2.
[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An anion exchange membrane, characterized in that Including polymers having structural units shown in formula I: In formula I, A is C, N or O, Cn is a C1-C5 alkylene group, and R1, R2, and R3 are each independently selected from a C1-C6 alkyl group.
2. The anion exchange membrane according to claim 1, characterized in that The polymer is a cross-linked body including the structural unit shown in formula I.
3. The anion exchange membrane according to claim 1 or 2, characterized in that: The anion exchange membrane includes a polyolefin porous membrane and the polymer filled in the pores of the polyolefin porous membrane.
4. The anion exchange membrane according to claim 3, characterized in that The thickness of the polyolefin porous membrane is 90 to 120 μm; And / or, the pore size of the polyolefin porous membrane is 1 to 1000 nm.
5. A method for preparing an anion exchange membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: Coating a raw material system including a monomer represented by Formula II on a substrate to initiate a polymerization reaction to obtain the anion exchange membrane; 6. The preparation method according to claim 5, characterized in that: The raw material system also includes a crosslinking agent, an initiator and / or a plasticizer; Preferably, the raw material system comprises 70 wt% to 89 wt% of the monomer represented by formula II, 5 wt% to 15 wt% of the crosslinking agent, 5 wt% to 10 wt% of the plasticizer and 1 wt% to 5 wt% of the initiator.
7. The preparation method according to claim 6, characterized in that: The cross-linking agent includes an aliphatic cross-linking agent, preferably ethylene glycol dimethacrylate; And / or, the plasticizer includes one or more of phthalates and fatty acid esters; And / or, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The polymerization reaction temperature is 80-100° C. and the reaction time is 6-8 hours.
9. The preparation method according to any one of claims 5 to 8, characterized in that: After the polymerization reaction is completed, the polymerization product is subjected to heat swelling treatment in water at 40 to 60°C.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The substrate is selected from a polyolefin porous membrane; Preferably, the thickness of the polyolefin porous membrane is 90 to 120 μm, and / or the pore size of the polyolefin porous membrane is 1 to 1000 nm.
Citation Information
Patent Citations
Method for preparing anion-exchange membrane with multi-crosslinked structure
CN109939572A
Homogeneous anion-exchange membrane, composite heterogeneous anion-exchange membrane, and composite homogeneous anion-exchange membrane
JP2012162728A
Manufacturing method of anion exchange membrane and anion exchange membrane using the same
KR101873260B1
Manufacturing method of anion-exchange membrane
KR1020150085202A
Polymer solar cell having cathode buffer layer including acid derivative modified conjugate polymer electrolyte
KR1020210131625A